Meningkatkan Kinerja Melalui Kebersamaan Guru Di SD Negeri 025 Indra Sakti - Supingi, Supingi (Komunitas Manajemen Kompetitif, 2017)
High performance, teachers will strive to overcome difficulties in the work, and vice versa low performance will reduce the enthusiasm of work, absenteeism, frequent displacement and complaints from teachers. Using the school action research and analyzed using qualitative methods, the research results after measuring the level of teacher performance in teaching through the application of the method of togetherness with the application of this cycle has an effect on the teacher performance improvement which was originally the teacher motivation is good enough amounted to 3 people or 7.7% increased to 30 people or 76.9%. Keywords: Teacher performance, togetherness